2005
DOI: 10.1021/cm0503679
|View full text |Cite
|
Sign up to set email alerts
|

Aerogel Synthesis of Yttria-Stabilized Zirconia by a Non-Alkoxide Sol−Gel Route

Abstract: Homogeneous, nanocrystalline powders of yttria-stabilized zirconia (YSZ) were prepared using a non-alkoxide sol−gel method. Monolithic gels, free of precipitation, were prepared by addition of propylene oxide to aqueous solutions of Zr4+ and Y3+ chlorides at room temperature. The gels were dried with supercritical CO2(l), resulting in amorphous aerogels that crystallized into stabilized ZrO2 following calcination at 500 °C. The aerogels and resulting crystalline products were characterized using in situ temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
114
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(119 citation statements)
references
References 45 publications
(85 reference statements)
4
114
1
Order By: Relevance
“…A conclusive advantage of the epoxide-mediated technique is that it allows the use of common metal salts as the sol-gel precursors, eliminating the need for highly reactive metal alkoxides. This technique has also proven to be useful in designing the precursor gels of highly homogensous complex oxides [20][21][22][23] . In this study, lithium acetate (CH 3 COOLi), iron nitrate nonahydrate (Fe(NO 3 ) 3 ?9 H 2 O), zirconium chloride (ZrCl 4 ), tetraethyl orthosilicate (Si(OC 2 H 5 ) 4 ) and phosphoric acid (H 3 PO 4 ) were used as the sources of inorganic components, and ethanol was used as the solvent.…”
Section: Methodsmentioning
confidence: 99%
“…A conclusive advantage of the epoxide-mediated technique is that it allows the use of common metal salts as the sol-gel precursors, eliminating the need for highly reactive metal alkoxides. This technique has also proven to be useful in designing the precursor gels of highly homogensous complex oxides [20][21][22][23] . In this study, lithium acetate (CH 3 COOLi), iron nitrate nonahydrate (Fe(NO 3 ) 3 ?9 H 2 O), zirconium chloride (ZrCl 4 ), tetraethyl orthosilicate (Si(OC 2 H 5 ) 4 ) and phosphoric acid (H 3 PO 4 ) were used as the sources of inorganic components, and ethanol was used as the solvent.…”
Section: Methodsmentioning
confidence: 99%
“…It is only recently that aerogel-like materials have been synthesized in electrically conductive, SOFC-relevant compositions and then characterized at operating temperatures. [11,12] An earlier sol-gel route to mixed La-Si oxides modified an acid-catalyzed silica sol-gel method by including lanthanum salts. [13,14] Investigation of a range of hydrolysis rates showed that only very narrow synthesis conditions led to apatite La 9.33 Si 6 O 26 upon calcination (800°C), [1] and impurity phases were common.…”
mentioning
confidence: 99%
“…This synthetic protocol is a modification of innovative methods reported by Gash et al for the preparation of transition metal oxide aerogels. [15][16][17] This route was recently extended to mixed transition metal oxide aerogels [11,18] and nanocomposites of silica and metal oxide. [19,20] We obtain gels by mixing tetramethoxysilane (TMOS) into methanolic solutions of LaCl 3 · 6H 2 O and then adding propylene oxide; the gels are processed as described in the Experimental section to form three different pore-solid nanoarchitectures.…”
mentioning
confidence: 99%
“…59,60 This is partly because of the stable and uniform dispersion of metal cations in the starting solution. Expanding this method, the generation of thermodynamic instability during the epoxide-mediated solgel polymerization enables well-defined macropores to be formed even in mixed oxide systems.…”
Section: Macropore Formation From Mixed Oxide Systemsmentioning
confidence: 99%